Peningkatan prestasi belajar Matematika materi Pecahan pada peserta didik kelas IV SD Negeri 1 Jebugan di semester gasal tahun pelajaran 2020/2021 melalui model pembelajaran Class Concern. - Warastuti, Nita Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to determine the increase in learning achievement in Mathematics on Fractions material in class IV students at SD Negeri 1 Jebugan in the odd semester of the 2020/2021 academic year through the Class Concern learning model. This research is classroom action research. Class concern learning is learning that focuses on teachers paying attention to activities in the class, using interactive, inspirational, fun, challenging and motivational principles so that students can learn actively. In cycle I there were 71% (5) students who completed KKM. The percentage of class average scores is still below the success indicators. Therefore, classroom action research was continued in the next cycle. The results of improvements in cycle II were 100% of students completing the KKM. The average student score is 72.9. Thus, the use of the Class Concern learning model succeeded in increasing learning achievement in Mathematics on Fraction material for class IV students at SD Negeri 1 Jebugan in the odd semester of the 2020/2021 academic year.